2014
DOI: 10.7860/jcdr/2014/8597.4512
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of MRSA, ESBL and AmpC – β -lactamases from Neonatal Sepsis at a Tertiary Care Hospital

Abstract: Background and Objectives: The emergence of methicillin resistant Staphylococcus aureus (MRSA) and extended spectrum β-lactamases (ESBLs) in neonatal intensive care unit patients is increasing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 18 publications
(11 reference statements)
4
30
1
Order By: Relevance
“…2 In present study, the most frequently isolated organism was Klebsiella pneumoniae 54 (26.34%) followed by S. aureus 36 (17.56%). Our findings were similar to Muley VA et al 18 K. pneumoniae was reported as a predominant pathogen in NNPD Report 2002-2003 and also by Sharma CM et al, Iregbu et al, Chelliah A et al and Tankhiwale SS et al 3,11,[27][28][29] K.pneumoniae and S. aureus can survive in the environment for a relatively long time and fairly widely distributed in the hospital environment and therefore have the potential for being transmitted from the environment to the patients through practices that breach infection control measures.…”
Section: Bacteriological Profile Of Neonatal Septicaemiasupporting
confidence: 81%
See 3 more Smart Citations
“…2 In present study, the most frequently isolated organism was Klebsiella pneumoniae 54 (26.34%) followed by S. aureus 36 (17.56%). Our findings were similar to Muley VA et al 18 K. pneumoniae was reported as a predominant pathogen in NNPD Report 2002-2003 and also by Sharma CM et al, Iregbu et al, Chelliah A et al and Tankhiwale SS et al 3,11,[27][28][29] K.pneumoniae and S. aureus can survive in the environment for a relatively long time and fairly widely distributed in the hospital environment and therefore have the potential for being transmitted from the environment to the patients through practices that breach infection control measures.…”
Section: Bacteriological Profile Of Neonatal Septicaemiasupporting
confidence: 81%
“…Our result matches with Chelliah A et al 11 who reported E. coli in 7.2% and P. aeruginosa in 10% of the cases respectively.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…In present study, 7(58%) were MRSA which were more than MSSA similar to Chelliah. A et al (18) (MRSA 56%) in contrast Kaistha.N et al (19) (11.11%).The higher rate of MRSA could, to a great extent be attributed to the fact that these organisms are now both hospital acquired and community flora. In present study all MRSA were 100% sensitive to Vancomycin.…”
Section: Objectivesmentioning
confidence: 99%